2019
DOI: 10.3390/su11174704
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Digital Content about Energy-Saving in Different Countries around the World

Abstract: Environmental sustainability is fundamental for human well-being, and energy-saving behaviors are fundamental for promoting environmental sustainability. This paper explores the types of information consumed on the Internet concerning the topic of energy-saving. The qualitative study used digital methods to analyze, from 17 different countries, one-year of Google searches, 170 webpages, and 6800 images. The results demonstrated that (a) most topics related to energy-saving involved commercial products; (b) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Research focused on preferences and future behavior, knowledge gathering, and trust building. The division into problems related to knowledge and trust was justified [71,80,81], because even the possessed knowledge did not result in the household managers trusting, for example, alternative energy sources. The research focused on the preferences and behaviors of household managers and was conducted using a representative method.…”
Section: Methodsmentioning
confidence: 99%
“…Research focused on preferences and future behavior, knowledge gathering, and trust building. The division into problems related to knowledge and trust was justified [71,80,81], because even the possessed knowledge did not result in the household managers trusting, for example, alternative energy sources. The research focused on the preferences and behaviors of household managers and was conducted using a representative method.…”
Section: Methodsmentioning
confidence: 99%
“…Ajzen has added the Perceived Behavior Control variable based on rational behavior theory, while Justin Paul et al have added environmental variables to the study of predicting the consumption of organic products to predict consumer behavior [27][28][29]. Chen and Tung have constructed a theoretical model of expanded plan behavior that includes environmental awareness and perceptual moral obligation [30][31][32]. Klöckner has proposed a comprehensive model using a meta-analytical approach to structural equation modeling, based on a pool of 56 different data sets with different target behaviors [33].…”
Section: Review Of Literaturementioning
confidence: 99%
“…To better exemplify how labels are obtained from an image, in Figure 1, an analysis made using Google Cloud Vision API is presented. Analyzing the characteristics of digital visual narratives related to the loss of energy on different natural disasters around the world can greatly contribute to increasing awareness about the lack of a more educational rhetoric around this issue, just as has been done in other studies to understand what is found when searching for "saving energy" on the web [31]. We believe that people's Analyzing the characteristics of digital visual narratives related to the loss of energy on different natural disasters around the world can greatly contribute to increasing awareness about the lack of a more educational rhetoric around this issue, just as has been done in other studies to understand what is found when searching for "saving energy" on the web [31].…”
Section: Literature Reviewmentioning
confidence: 99%